2010
DOI: 10.1523/jneurosci.4297-10.2010
|View full text |Cite
|
Sign up to set email alerts
|

Spinal Interneurons Facilitate Coactivation of Hand Muscles during a Precision Grip Task in Monkeys

Abstract: Grasping is a highly complex movement requiring coordination of a number of hand joints and muscles. In contrast to cortical descending systems, the contribution of the subcortical system for coordinating this higher degree of freedom is largely unknown.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
93
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 105 publications
(97 citation statements)
references
References 65 publications
(82 reference statements)
3
93
1
Order By: Relevance
“…Two macaque monkeys were trained to perform a precision grip task, in which they were required to grip and release two springloaded levers with their index finger and thumb to target positions (12,16). During the task, we recorded single-unit activity from cervical spinal neurons and electromyographic (EMG) activity from 12 hand muscles (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Two macaque monkeys were trained to perform a precision grip task, in which they were required to grip and release two springloaded levers with their index finger and thumb to target positions (12,16). During the task, we recorded single-unit activity from cervical spinal neurons and electromyographic (EMG) activity from 12 hand muscles (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…We previously showed that PreM-INs in monkey cervical cords have divergent postspike effects on a group of hand muscles during a precision grip task, termed the neuron's "muscle field" (12). This finding suggests that PreM-INs contribute to the synergistic control of primate hand movements (9,(13)(14)(15), but this question has not been examined directly.…”
mentioning
confidence: 99%
“…In primates and rodents there is evidence for the role of spinal interneurons in regulating hand movements. [30][31][32] Our injury paradigm results in significant loss of GM in the C6 region, which contains motor neurons and interneurons that make up spinal circuits responsible for forelimb and hand movement. We propose that permanent neuronal loss in forelimb spinal circuits results in functional deficits that cannot be overcome by natural recovery.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the main effect of the so called corticospinal tract is not exerted directly on the motorneurons innervating the muscle, but rather indirectly via a large pool of premotor spinal interneurons (Jankowska 1992;Bortoff and Strick 1993;Isa et al 2006;Alstermark et al 2007). Also, spinal premotor neurons have a divergent innervation to target multiple motorneuron pools (Alstermark et al 1991;Jankowska 1992;Takei and Seki 2010). In other words, all connections, which serve as the infrastructure for neural motor control is naturally synergistic, i.e.…”
Section: The Neuroscience Of Graspingmentioning
confidence: 99%